Mapping Reproductive Health of Indigenous Women in India: A Systematic Review - Rai, Shikha; Chakraborty, Rupsha; Chand, Dipannita (Italian Sociological Review, 2025)
Reproductive health among Indigenous women is a multifaceted issue involving socio-cultural, economic and systematic factors. The present work aims to systematically review and synthesize existing research on reproductive health of Indigenous women in India. It addresses two interconnected research questions: their perception towards family planning & contraceptive usage and their accessibility to reproductive healthcare resources. Accordingly, a comprehensive search initially yielded 15,058 articles and later reduced to 669 after applying inclusion criteria like content accessibility, publication time frame, language and subject focus. In order to make the review country-specific, 62 articles related to India were identified. After screening the title, abstract and full-text, 17 articles were finally reviewed. The review highlights reproductive healthcare barriers faced by Indigenous women due to factors such as spatial, socio-economic status, and cultural & traditional values. It also identifies the importance of awareness regarding family planning and contraceptive uses. With reference to healthcare provision for Indigenous women, it stresses on the accessibility and quality of care as well as culturally appropriate reproductive healthcare. The review also emphasises the evident need for collaborative work between policymakers and healthcare providers in order to address such challenges and achieve equitable and comprehensive reproductive healthcare for Indigenous women.